Israel's Roaring Economy - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2007)
Many observers of the Israeli scene have been perplexed by the country's apparent resilience to bad political news. The headlines of late seem uniformly dreadful. While the country is still licking its wounds from a botched, if not humiliating war with Hezbollah, the Palestinian territories again slide into turmoil, and the experts rumour yet another conflict with Syria. The U.S. entanglement is Iraq and Afghanistan is only getting deeper, and many speak of an imminent attack on Iran with untold regional consequences. Israeli politicians and public officials – from the president, through the prime minister, to the chief of staff, to the justice minister – have been embroiled in corruption and other scandals. The courageous capitalist media routinely expose government officials as incompetent crooks and the Israelis Parliament as an irrelevant institution. And yet, none of these headlines seem to impact the economy. It's roaring. Many commentators have been trying to make sense of this apparent puzzle. But their explanations, whether plausible or not, all fall into the same trap: they believe the capitalist media. They rush to explain why the Israeli economy is roaring without ever stopping to ask whether it is roaring.
Keywords: 330; capital; finance; growth; Israel; ownership; measurement; neoclassical economics; stock market; transnationalization